HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA KELAS V SDN 001 AIRTIRIS KECAMATAN KAMPAR - Eka Saputra; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s of Student In class V Of SDN 001 Air Tiris Kampar District, research found the result of long jump the student in class V of SDN 001 Air Tiris was not optimal yet. Evident from learning outcomes still below average or below standars that class rise to minimal completeness criteria. The purpose of this research is to see The correlation of explosive power leg muscles with the long jump results with squat style of student in class V Of SDN 001 Air Tiris Kampar District. Population in this research is all students in class V of SDN 001 Air Tiris amount 63 people, 33 male students and 30 female students. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 63 people. Research instrument used standing board jump test and long jump test with squat style. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : Shows that there is correlation of explosive power leg muscle with the long jump results with squat style of male student which shows correlation rxy > rtabel(0,506>0,347) and there is correlation of explosive power leg muscle with the long jump results with squat style of female student which shows correlation rxy > rtabel(0,521>0,367)Key word : explosive power leg muscles, long jump.